Failure Analysis of YBCO Tapes Considering the Amplitude and Duration of Sinusoidal Overcurrent - Chen, Guilun; Ren, Li; Xu, Ying; Yan, Sinian; Liang, Siyuan; Pu, Dongsheng; Wang, Wei; Hu, Ziheng; Zhang, Bin; Li, Jingdong; Shi, Jing; Tang, Yuejin (IEEE transactions on applied superconductivity, 2019)
The ultimate current-carrying capacity of high-temperature superconducting (HTS) tapes is extremely important for the design of superconducting devices, especially for superconducting fault current limiter and HTS cables which may be subject to short-circuit overcurrent. In this paper, an HTS tape life characteristics test platform was built, and experiments were carried out on the YBCO tape to study its ultimate current-carrying characteristic under 50 Hz ac current. AC overcurrent amplitude and duration are used as experimental variables. According to the single variable method, the current and voltage of the YBCO tapes under different types of overcurrent were measured. After analyzing and generalizing the test results, the thresholds of its bearable current and corresponding duration are discussed. This paper provides data support and reference for the reliable design of these HTS power devices.